SISTEM INFORMASI KELOMPOK TANI KECAMATAN DANAU KERINCI PADA KANTOR UNIT PELAKSANA TEKNIS DINAS (UPTD) KECAMATAN DANAU KERINCI - Sophan Sophian (ITP Press)
At the Office of Technical Implementation Unit (UPTD) Lake Kerinci District of farmer groups in data processing as well as the report, still using Microsoft Excel and Microsoft Word. There are several obstacles that obtained by using this system, among others, is the difficulty in detecting errors in the data entered (input), and often lead to data redundancy, as well as difficulty finding are cordor data desired. Seeing the problems above, the proposed implementation of an application program that developed into a program of data processing applications with a Web-based farmer groups store the data into a database that can facilitate the dbkelompok tani UPTD Agriculture farmer groups in data processing and deliver reports quickly and timely. With the construction ofcomputer-based applications, it is expected thatallexistingbarrierscan beovercome with good and can further improve service to the community quickly to realize a system that is effective and efficient. This applicationhasmore advantagescompared tothe oldsystemare:Canthe target areaof dataprocessing, the data leading commodity, the data management, and data quickly farmer groups. Web-based applications. Provide reports target area, leading commodity reports, board reports, reports overall farmer groups, farmer groups and reports based on the name of the target area.